The influence of virtual reality as a therapeutic tool for low back pain in young adults (Research, Society and Development, 2021)
Objective: Evaluate to use of virtual reality as a tool therapeutic for low pain back in adults young. Methods: The study is almost experimental, descriptive, and quantitative cross-sectional, with the participation of 6 female subjects, aged between 20 and 25 years. The postural assessment was performed using the Software of Postural Analysis (SAPO) and the application of the Oswestry Disability Index (ODI) to assess work limitations and difficulties, before and after the ten (10) Nintendo Wii sessions. As well as the Visual Analogue Scale (VAS) was used in all sessions before and after using the Nintendo Wii to assess pain intensity. Results: The participants obtained variation in low back pain through VAS, during the evaluation, four (4) of the individuals reported moderate low back pain and after the 10 sessions all volunteers did not pain present. And also, a satisfactory evolution of capacity functional. However, there were no changes postural in the study participants. Conclusion: From the results found, it is suggested that there are signs of improvement after using Virtual Reality through the Nintendo Wii. Despite this, it is recommended that there be replications of this study with a larger and more diverse sample to reinforce the evidence obtained in this research.